A smart DNA–gold nanoparticle probe for detecting single-base changes on the platform of a quartz crystal microbalance1. Issue 22 (18th March 2015) - Li, Hui; Xiao, Shiyan; Yao, Dongbao; Lam, Michael Hon-Wah; Liang, Haojun
<x xml:space="preserve">Abstract</x> A design of DNA–gold nanoparticle probe-fueled DNA strand displacements for detecting single-base changes on the platform of a quartz crystal microbalance with random sequences was developed.